2021
DOI: 10.1159/000518801
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epigenetic Therapy in the Modulation of Tumor Growth and Migration in Human Castration-Resistant Prostate Cancer Cells with Neuroendocrine Differentiation

Abstract: <b><i>Introduction:</i></b> Neuroendocrine transdifferentiation (NED) of prostate cancer (PC) cells is associated with the development of resistance to antiandrogen therapy and poor prognosis in patients with castration-resistant PC (CRPC). Many of the molecular events, involved in NED, appear to be mediated by epigenetic mechanisms. In this study, we evaluated the antitumor activity and epigenetic modulation of 2 epigenetic drugs, such as the demethylating agent 5-aza-2′-deoxycytidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…It has been previously reported that DU-145 and PC-3 cells are androgen-independent cell lines [ 34 ], and C4-2B cells are androgen receptor-positive but androgen-independent [ 35 ]. All three cell lines possess a tendency to develop NE characteristics [ 36 , 37 ]. Thus, we employed SOX4-high-expressing DU-145 and PC-3 cells to construct SOX4-knockdown subclone cell lines and selected SOX4-low-expressing C4-2B cells to construct SOX4-overexpressing subclone cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that DU-145 and PC-3 cells are androgen-independent cell lines [ 34 ], and C4-2B cells are androgen receptor-positive but androgen-independent [ 35 ]. All three cell lines possess a tendency to develop NE characteristics [ 36 , 37 ]. Thus, we employed SOX4-high-expressing DU-145 and PC-3 cells to construct SOX4-knockdown subclone cell lines and selected SOX4-low-expressing C4-2B cells to construct SOX4-overexpressing subclone cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…After 3 days of incubation, cell culture medium was replaced with a fresh one containing vehicle or drug at different concentrations. After 6 days, cells were analyzed using MTT (for NCI-H727 and UMC-11) or MTS (for NCI-H835 and NCI-H720) assays, as previously described [27,28].…”
Section: Cell Viability Assaymentioning
confidence: 99%